Uji Efektivitas Sediaan Nanoparticle Lipid Carrier (NLC) Kombinasi Ekstrak Teh Hijau dan Asam Alfa-Lipoat sebagai Antiaging - Abdurrahman, Abdurrahman; Afra, Fairuz Yaumil; Soeratri, Widji; Purwanto , Djoko Agus (Journal of Pharmaceutical and Sciences, 2025)
Background: Alpha-lipoic acid acts as a co-antioxidant that may enhance the effectiveness of green tea extract as an antiaging agent in a Nanostructured Lipid Carrier (NLC) system by improving its entrapment efficiency. This combination is expected to enhance antiaging benefits through increased collagen density and fibroblast proliferation in the skin. Objective: This study aimed to evaluate the effectiveness of an NLC formulation combining green tea extract and alpha-lipoic acid as an antiaging agent. Methods: The NLC system was prepared using the high-shear homogenization method with three formulations: F1 (without alpha-lipoic acid), F2 (1% alpha-lipoic acid), and F3 (1.5% alpha-lipoic acid). The efficacy test was conducted in vivo using mice, with observed parameters including collagen density and fibroblast count in the dorsal skin over 14 days. Results: The results demonstrated that F2 and F3 exhibited significantly higher collagen density and fibroblast counts compared to F1, indicating that the addition of alpha-lipoic acid enhances antiaging efficacy. Conclusion: This study confirms that the NLC formulation combining green tea extract and alpha-lipoic acid effectively increases collagen density and fibroblast proliferation, suggesting its potential as a superior antiaging agent compared to formulations without the co-antioxidant.